From A to B (and Back again) : A publication to accompany the exhibition Go Away : Artists and Travel. - Bamgboyé, Oladélé Ajiboyé; Blissett, Luther; Butor, Michel; Calderón, Miquel; Calvino, Italo; Carolin, Clare; Craze, Ben; Dippel, Rini; Fricke, Harald; Fulton, Hamish; Gladwin, Peter; Gleadowe, Teresa; et al. (London : Royal College of Art Galleries, 1999)
Ackermann, Franz ; Alÿs, Francis ; Association of Autonomous Astronauts ; Bamgboyé, Oladélé Ajiboyé ; Best, Anna ; Blissett, Luther ; Brouwn, Stanley ; Calderon, Miguel ; Calvino, Italo ; Dean, Tacita ; Doig, Peter ; Ehrenberg, Felipe ; Fluxshoe ; Framis, Alicia ; Fulton, Hamish ; Graham, Rodney ; de Gruyter, Voebe ; Héllion, Martha ; Huebler, Douglas ; Hughes, Dean ; Inventory ; Jarman, Derek ; Leeds 13 ; Liss, Carla ; Lloyd, Hilary ; LPA Historification Committee ; Long, Richard ; Unlimited, Loompanics ; McLean, Bruce ; Maciunas, George ; Mackenna, Tracy ; Janssen, Edwin ; Medalla, David ; Milroy, Lisa ; Perec, Georges ; Genesis, P. Orridos ; Siegelaub, Seth ; Skála, Frantisek ; Smithson, Robert ; Tan, Fiona ; Tiravanija, Rirkrit ; Ulay ; Urban, Janos ; Winstanley, Paul ; Wolski, Tristan
biografie
From A to B (and Back again), Royal College of Art Galleries, London, 17 April - 9 May 1999
Engels
boek